2021
DOI: 10.1111/cmi.13376
|View full text |Cite
|
Sign up to set email alerts
|

TheHelicobacter pyloritypeIVsecretion system upregulates epithelial cortactin expression by aCagA‐ andJNK‐dependent pathway

Abstract: Cortactin represents an important actin‐binding factor, which controls actin‐cytoskeletal remodelling in host cells. In this way, cortactin has been shown to exhibit crucial functions both for cell movement and tumour cell invasion. In addition, the cortactin gene cttn is amplified in various cancer types of humans. Helicobacter pylori is the causative agent of multiple gastric diseases and represents a significant risk factor for the development of gastric adenocarcinoma. It has been repeatedly shown that H. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 109 publications
0
7
0
Order By: Relevance
“…In line with these observations, complete cortactin knockout strongly diminished this phenotype (Knorr et al, 2021). Moreover, H. pylori upregulate the expression of cortactin via translocated CagA in a c‐Jun N‐terminal kinase (JNK)‐dependent manner, which inhibits Snail1, a controller of cttn gene expression, and promotes stabilization of cortactin by paxillin and FAK to protect it from degradation (Figure 2d) (Sharafutdinov et al, 2021a). The pathogen furthermore manipulates cortactin phosphorylation (Sharafutdinov et al, 2020).…”
Section: Gram‐negative Bacteriamentioning
confidence: 99%
“…In line with these observations, complete cortactin knockout strongly diminished this phenotype (Knorr et al, 2021). Moreover, H. pylori upregulate the expression of cortactin via translocated CagA in a c‐Jun N‐terminal kinase (JNK)‐dependent manner, which inhibits Snail1, a controller of cttn gene expression, and promotes stabilization of cortactin by paxillin and FAK to protect it from degradation (Figure 2d) (Sharafutdinov et al, 2021a). The pathogen furthermore manipulates cortactin phosphorylation (Sharafutdinov et al, 2020).…”
Section: Gram‐negative Bacteriamentioning
confidence: 99%
“…Afterwards, serine-phosphorylated cortactin induces the auto-phosphorylation of FAK at tyrosine 397, which triggers a signaling pathway involving the activation of Src and Abl kinases, which results in the pronounced phosphorylation of injected CagA [49]. Furthermore, it was shown that H. pylori triggers cortactin overexpression at the protein level in a CagA-and JNK-dependent manner, which can be associated with gastric carcinogenesis [63]. However, other H. pylori virulence factors such as VacA have also been reported to target cortactin.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to probing, the PVDF membranes were blocked with either 3% BSA or 5% non-fat dry milk in TBST, depending on the primary antibody and manufacturers instructions [70]. Primary antibodies used were specific against cortactin (Merck-Millipore, Darmstadt, Germany #05-180), GAPDH (Santa Cruz, Heidelberg, Germany, #SC-47724), CagA (Austral Biologicals, San Ramon, CA, USA, #HPP-5003-9), CagE [63], VacA [34], FlaA [71], RPTP-α (Santa Cruz, #SC-28907), integrin-β1 (Santa Cruz, #SC-H96), full-length caspase-3 (Cell Signaling Technology, Frankfurt, Germany, #9668) and active caspase-3 (Cell Signaling Technology, #9664). Secondary antibodies detected either mouse (Invitrogen, Darmstadt, Germany, #31446) or rabbit (Invitrogen, #31460) primary antibodies and were coupled to horseradish peroxidase.…”
Section: Sds-page and Immunoblot Analysismentioning
confidence: 99%
“…However, it is still unclear whether the instability of the HopQ–CEACAMs relationship favors the host or the bacterium, so more studies are needed to investigate the possibility of these interactions being beneficial in favor of the patient infected with H. pylori. BabA is apparently also capable of increasing T4SS activity[ 55 ].…”
Section: Caga — H Pylori Translocated Oncoproteinmentioning
confidence: 99%